Linguistic landscape and power representation at gas stations - Wahyuni, Sri; Kurniati, Ai; Susilawati, Dyah (LITERA, 2024)
Gas stations are hazardous, highly flammable public places. Thus, signs containing prohibitions, warnings, information, and road directions are needed to prevent catastrophes. This study aims to identify the linguistic system of the signs and describe the representation of power through the signs. The research site is gas stations in Semarang. This study uses observation methods in data collection by documenting, sorting, and classifying data using a national language, region, foreign, or both based on the linguistic system. Spolsky and Cooper's (1991) taxonomy of signs is used to classify the data. The categories are then examined further to reveal the embedded power relations. The results show that the linguistic landscape at the gas stations uses a monolingual system, Indonesian. This system demonstrates the gas station authorities' concern about prioritizing the state language in public spaces. Suggestions embedded in the signs do not explicitly represent power relations. However, they represent power by removing the subjects and objects on these signs. Texts of prohibitions and warnings should be created by involving more people so that the texts on the gas station LL can be more user-friendly.